Penerapan Algoritma Particle Swarm Optimization (PSO) pada Sistem Penjadwalan Kegiatan Mentoring Baca Tulis Al-Qur'an - Serliana Serliana; Rahman Rahman; Hastuti Hastuti; Farida Yusuf; A. Mustika Abidin (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The application of algorithms in the mentoring activity scheduling system is an innovative solution to overcome the complexity of time and resource management. This study aims to develop a mentoring activity scheduling system for Reading and Writing the Qur'an (BTQ) using the particle swarm optimization (PSO) algorithm. The PSO algorithm was chosen because of its ability to find optimal solutions efficiently through a particle population approach. This system is designed to meet the schedule preferences of students and supervisors, taking into account the limited time available and the interrelationships between schedules. This study makes a significant contribution to improving the efficiency of BTQ mentoring activity scheduling, as well as demonstrating the potential of PSO in solving other scheduling problems.